Trust and security risks in mobile banking - Messaggi Kaya, M (2013)
With the development and growth of mobile technologies, mobile phones enable users to perform a number of different tasks with their devices: from sending simple text messages, checking e-mails and browsing the internet, to running elaborated applications. Nowadays, the mobile phone platform creates great opportunities for businesses, especially due to its capabilities and population coverage: the number of mobile subscriptions approaches global population figures. In order to explore such opportunities, most banks have already launched their mobile applications and/or re-designed mobile version of their websites. One of the benefits of using mobile banking is the possibility for users to carry out bank transactions, such online payments or transfers, at anytime and anywhere. Expectations for the adoption of mobile banking were high; however, it represents about 20% of mobile phone users at the present. One factor has been recognised as being a strong reason for users not to adopt mobile banking: their concerns about security. This dissertation focuses on the relationship between the trust users have in mobile banking and the security risks that the use of mobile devices potentially pose. A questionnaire was created in order to gather users’ perception of security about mobile banking, and its results compared with recognised security issues.